The book of Acts - VanDen Bergh, Regardt; Arnold, Jones Henry O.; O'neil, Jennifer; Quinn, Francesco; Marchiano, Bruce; Brolin, James (Brentwood, Tenn : Visual International, 1997)
The only dramatization of the Church in its beginnings, using the actual Scriptures as related through the book of Acts, word for word, from the New International Version.
DVD ; Dolby, digital surround 5.1.
Executive producer: Charles K. Robertson; Producer: Robert Marcarelli; Director: Regardt van den Bergh.
Keywords: Apostles -- Drama; Paul, The Apostle, Saint -- Drama; Church history -- Primitive and early church,30-600